(untitled) (Mill Valley, California, 1994)
A textbook for a one-quarter or one-semester course in bioinorganic chemistry for advanced undergraduate and graduate students in chemistry or biochemistry. At a more advanced level than other bioinorganic textbooks, the chapters teach the underlying principles of bioinorganic chemistry as well as outlining the state of knowledge in selected areas.
Hóa vô cơ sinh hóa
Keywords: Hóa sinh học vô cơ,Bioinorganic chemistry